Nanosheet light-emitting detection device and preparation method thereof

CN123035828APending Publication Date: 2026-11-03SUN YAT SEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611248440.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing nanosheet devices struggle to achieve hole injection and charge balance in a single device, making it difficult to achieve efficient integration of light emission and photodetection functions.

Method used

A bilayer structure with a first hole injection layer and a second hole injection layer between the hole transport layer and the anode is adopted to adjust the charge distribution and improve the balance between hole injection and charge injection. The active layer of the nanosheet serves as the light-emitting layer under forward bias and as the light-absorbing layer under reverse bias, thereby achieving efficient integration of light emission and light detection functions.

Benefits of technology

The system achieves efficient integration of light emission and photodetection functions in a single device structure, improving both light emission efficiency and photodetection performance, and combining high-efficiency light emission with wide-spectrum, fast photodetection capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123035828A_ABST
    Figure CN123035828A_ABST
Patent Text Reader

Abstract

The application discloses a nanosheet light-emitting detection device and a preparation method thereof. The device comprises a substrate and a light-emitting detection laminated structure arranged on the substrate. The light-emitting detection laminated structure comprises a cathode, an electron transport layer, a nanosheet active layer, a hole transport layer, a first hole injection layer, a second hole injection layer and an anode which are sequentially stacked. The nanosheet active layer comprises nanosheets prepared by a solution method. The device has the dual functions of efficient deep red light-emitting and wide-spectrum light detection in a single structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of semiconductor optoelectronic device technology, and in particular to a nanosheet light-emitting detector and its fabrication method. Background Technology

[0002] With the rapid development of high-performance computing, data center optical interconnects, and intelligent sensing systems in the post-Moore era, optoelectronic systems have placed higher demands on miniaturization, low power consumption, and high integration. Integrating multiple optoelectronic functions, such as light emission and light detection, into a single device has become an important direction for building the next generation of multifunctional optoelectronic systems.

[0003] Currently, most mainstream optoelectronic integration technologies are based on silicon-based photonics or III-V compound semiconductor processes, which typically require high-temperature vacuum environments, resulting in complex processes, high costs, and difficulty in large-scale fabrication on flexible or large-area substrates. Solution-prepared nanocrystalline materials can be deposited into films using low-temperature liquid-phase processes and are suitable for various substrates. Among these, nanosheets are two-dimensional colloidal nanocrystals with atomic-level thickness and strong quantum confinement, exhibiting narrow full width at half maximum (FWHM) photoluminescence, large absorption cross-section, and anisotropic optical properties, showing potential applications in devices such as light-emitting diodes (LEDs) and photodetectors.

[0004] However, most existing research on nanosheet devices focuses on optimizing either light emission or light detection performance separately, and there are still limited options for using the same device for both light emission and light detection. In addition, in the inverted device structure, due to the relatively low work function of the anode, it is difficult to inject holes into the light-emitting layer, resulting in poor charge injection balance, which restricts further improvement of device performance.

[0005] Therefore, how to improve hole injection and charge balance in a single nanosheet device and achieve efficient integration of light emission and photodetection functions has become a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0006] The purpose of this application is to overcome the shortcomings of the prior art and provide a nanosheet light-emitting detector and its preparation method, so as to solve the technical problem that existing nanosheet devices are difficult to improve hole injection and charge balance in a single device and achieve efficient integration of light emission and light detection functions.

[0007] To achieve the above objectives, this application adopts the following technical solution:

[0008] In a first aspect, this application provides a nanosheet light-emitting detector device, characterized in that it includes a substrate and a light-emitting detector stacked structure disposed on the substrate; the light-emitting detector stacked structure includes a cathode, an electron transport layer, a nanosheet active layer, a hole transport layer, a first hole injection layer, a second hole injection layer and an anode stacked sequentially.

[0009] In one possible implementation, the active layer of the nanosheet includes nanosheets prepared by solution method, wherein the nanosheets are quasi-type II heterojunction nanosheets with a core-crown structure.

[0010] In one possible implementation, the material of the first hole injection layer is one or more of MoO3, WO3, and V2O5.

[0011] In one possible implementation, the material of the second hole injection layer is one or more of HAT-CN and HAT-CN derivatives.

[0012] In one possible implementation, the absolute values ​​of the differences between the lowest unoccupied energy level of the first hole injection layer and the lowest unoccupied energy level of the second hole injection layer and the highest occupied energy level of the hole transport layer are both no greater than 0.6 eV, so that the first hole injection layer and the second hole injection layer extract electrons from the hole transport layer.

[0013] In one possible implementation, the electron transport layer is made of one or more of PO-T2T, TPBI, ZnO, ZnMgO, and SnO2; and the hole transport layer is made of one or more of PEDOT:PSS, CBP, PVK, TFB, Poly-TPD, PF8Cz, mCP, BCBP, 26DCZPPy, TCTA, TAPC, NPB, TPD, and m-MTDATA.

[0014] In one possible implementation, the second hole injection layer is located between the first hole injection layer and the anode, and the thickness of the first hole injection layer is 0.5-20 nm, while the thickness of the second hole injection layer is 1-200 nm.

[0015] In one possible implementation, the active layer of the nanosheet is configured to: perform electroluminescence as a light-emitting layer under forward bias, and absorb incident light and generate photocurrent as a light-absorbing layer under reverse bias.

[0016] In a second aspect, this application provides a method for fabricating a nanosheet light-emitting detector, characterized in that the method for fabricating the nanosheet light-emitting detector according to any one of the first aspects includes the following steps: forming a cathode on a substrate; forming an electron transport layer on the cathode; forming a nanosheet active layer on the electron transport layer; forming a hole transport layer on the nanosheet active layer; forming a first hole injection layer on the hole transport layer; forming a second hole injection layer on the first hole injection layer; and forming an anode on the second hole injection layer.

[0017] In one possible implementation, the electron transport layer, the nanosheet active layer, the hole transport layer, the first hole injection layer, and the second hole injection layer are each formed independently by any one of the following processes: spin coating, blade coating, nanoimprinting, printing, and vapor deposition.

[0018] In one possible implementation, the first hole injection layer, the second hole injection layer, and the anode are continuously formed by vapor deposition in a vacuum environment.

[0019] The beneficial effects of this application are as follows: by sequentially setting a first hole injection layer and a second hole injection layer between the hole transport layer and the anode to form a dual hole injection layer structure, the potential barrier for the anode to inject holes into the hole transport layer is reduced and the charge distribution within the device is adjusted, thus improving the balance between hole injection and charge injection; the nanosheet active layer acts as a light-emitting layer to achieve electroluminescence under forward bias and as a light-absorbing layer to absorb incident light and generate photocurrent under reverse bias. The two share the same carrier transport channel. Therefore, this application achieves efficient integration of light emission and photodetection functions in a single device structure, possessing both high-efficiency light emission and wide-spectrum, fast photodetection functions. Attached Figure Description

[0020] Figure 1 A schematic diagram of the stacked structure of the nanosheet light-emitting detector device provided in this application;

[0021] Figure 2 This is a schematic diagram of the structure of the nanosheet light-emitting detector provided in this application;

[0022] Figure 3 A schematic diagram of the energy level structure of the nanosheet light-emitting detector provided in this application;

[0023] Figure 4 Characterization results of the nanosheets provided in this application;

[0024] Figure 5 Luminescence performance diagrams of nanosheet light-emitting detectors with different hole injection structures provided in this application;

[0025] Figure 6 The detection performance diagram of the nanosheet light-emitting detector based on the first hole injection layer / anode structure provided in this application;

[0026] Figure 7 The detection performance diagram of the nanosheet light-emitting detector based on the first hole injection layer / second hole injection layer / anode structure provided in this application. Detailed Implementation

[0027] The present application will be further described in detail below with reference to the accompanying drawings and embodiments. However, the implementation of the present application is not limited thereto.

[0028] See Figure 1 and Figure 2 This application provides a nanosheet light-emitting detector device, which includes a substrate 1 and a light-emitting detector stacked structure disposed on the substrate 1. The light-emitting detector stacked structure includes a cathode 2, an electron transport layer 3, a nanosheet active layer 4, a hole transport layer 5, a first hole injection layer 6, a second hole injection layer 7, and an anode 8, stacked sequentially from one side of the substrate 1 outwards. In this embodiment, the cathode 2 is disposed on the substrate 1, forming an inverted structure. The nanosheet active layer 4 includes nanosheets, and further, the nanosheet active layer 4 includes nanosheets prepared by solution method (solution method refers to a low-temperature processing method in which nanosheets are synthesized in a colloidal solution and then the solution is used to form a film on a substrate by spin coating, blade coating, or printing, etc.), and the nanosheets are quasi-type II heterojunction nanosheets with a core-crown structure ( Figure 2 The CQW in the text refers to nanosheets, where holes are mainly confined to the core and electrons are distributed throughout the structure, thus achieving deep red emission.

[0029] In some embodiments, the substrate 1 is an alkali-free glass substrate or a flexible transparent substrate, so that the electroluminescent light is emitted through the substrate 1.

[0030] In some embodiments, the cathode 2 is a transparent electrode made of ITO.

[0031] In some embodiments, the electron transport layer 3 is made of one or more of PO-T2T, TPBI, ZnO, ZnMgO and SnO2, preferably ZnO; the electron transport layer 3 is used to transport electrons injected from the cathode 2 to the nanosheet active layer 4.

[0032] In one possible implementation, the absolute values ​​of the differences between the lowest unoccupied energy level of the first hole injection layer and the lowest unoccupied energy level of the second hole injection layer and the highest occupied energy level of the hole transport layer are both no greater than 0.6 eV, so that the first hole injection layer and the second hole injection layer extract electrons from the hole transport layer.

[0033] In some embodiments, the hole transport layer 5 is made of one or more of PEDOT:PSS, CBP, PVK, TFB, Poly-TPD, PF8Cz, mCP, BCBP, 26DCZPPy, TCTA, TAPC, NPB, TPD, and m-MTDATA, preferably TCTA; the hole transport layer 5 is used to transport holes injected by the anode 8 to the nanosheet active layer 4.

[0034] In some embodiments, the first hole injection layer 6 is a p-type oxide inorganic semiconductor, the material of which is selected from one or more of MoO3, WO3 and V2O5, preferably MoO3, and the thickness is 0.5-20nm, preferably 6nm.

[0035] In some embodiments, the material of the second hole injection layer 7 is one or more of HAT-CN (2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazabenzophenanthrene) and HAT-CN derivatives, preferably HAT-CN, and the thickness is 1-200 nm, preferably 6 nm.

[0036] HAT-CN derivatives refer to compounds with hexaazatriphenylene oxide as the parent nucleus and one or more strongly electron-withdrawing substituents on its aromatic ring. These strongly electron-withdrawing substituents include one or more of cyano, fluorine, chlorine, and trifluoromethyl groups. These derivatives retain the electron-deficient characteristics of the HAT-CN parent nucleus, and their lowest unoccupied energy level is similar to that of HAT-CN (approximately 5.0–5.4 eV, with reference to the vacuum level). They can attract electrons from adjacent hole transport layers 5 to increase the hole concentration; furthermore, they exhibit good molecular thermal stability and can be deposited into films via vacuum evaporation, thus also meeting the requirements for serving as the second hole injection layer 7.

[0037] In some embodiments, the anode 8 is made of one or more of Ag, Al, Mg, Mo, ITO and Cr / Au stacks, preferably Al.

[0038] See Figure 3In the inverted structure, due to the relatively low work function of the anode 8, it is more difficult to inject holes into the hole transport layer 5. Referring to Figure 3, with the vacuum energy level as a reference, the energy levels of each functional layer in this embodiment are as follows: the work function of cathode 2 (ITO) is approximately 4.9 eV; the lowest unoccupied energy level of electron transport layer 3 (ZnO) is approximately 3.97 eV, and the highest occupied energy level is approximately 7.45 eV; the electronic energy level of nanosheet active layer 4 is approximately 3.96 eV, and the hole energy level is approximately 5.93 eV; the lowest unoccupied energy level of hole transport layer 5 (TCTA) is approximately 2.28 eV, and the highest occupied energy level is approximately 5.67 eV; the lowest unoccupied energy level of first hole injection layer 6 (MoO3) is approximately 6.17 eV, and the highest occupied energy level is approximately 9.52 eV; the lowest unoccupied energy level of second hole injection layer 7 (HAT-CN) is approximately 5.14 eV, and the highest occupied energy level is approximately 9.16 eV; and the work function of anode 8 (Al) is approximately 4.3 eV. As can be seen from the above energy levels, the absolute values ​​of the differences between the lowest unoccupied energy levels (approximately 6.17 eV and 5.14 eV) of the first hole injection layer 6 and the second hole injection layer 7 and the highest occupied energy level (approximately 5.67 eV) of the hole transport layer 5 are approximately 0.50 eV and 0.53 eV, respectively, neither exceeding 0.6 eV. Therefore, electrons in the hole transport layer 5 are easily extracted by the first hole injection layer 6 and the second hole injection layer 7. Furthermore, the highest occupied energy levels (approximately 9.52 eV and 9.16 eV) of the first hole injection layer 6 and the second hole injection layer 7 are much deeper than the highest occupied energy level (approximately 5.67 eV) of the hole transport layer 5, differing by approximately 3.85 eV and 3.49 eV, respectively. Therefore, hole injection on the anode side is not a direct injection between the highest occupied level of the injection layer and the hole transport layer, but mainly manifests as the injection layer extracting electrons from the hole transport layer and collecting them by the anode 8 through the thinner injection layer. The mechanism by which the dual hole injection layer improves hole injection includes the following two aspects. First, the dual hole injection layer structure of the first hole injection layer 6 and the second hole injection layer 7 decomposes the energy level difference between the anode 8 and the hole transport layer 5 into two smaller step barriers, which is more conducive to hole injection than a single hole injection layer; at the same time, the interface between the anode 8 and the second hole injection layer 7 forms an interface dipole, which enhances the hole injection capability under bias voltage, and the interface between the first hole injection layer 6 and the hole transport layer 5 forms a p-type doped and charge transfer complex, which further promotes hole injection. Second, the HOMO levels of the first hole injection layer 6 and the second hole injection layer 7 are both relatively deep and differ significantly from the HOMO level of the hole transport layer 5. However, their LUMO level is close to the HOMO level of the hole transport layer 5. Therefore, hole injection at the anode 8 is essentially a process in which the injection layer extracts electrons from the hole transport layer 5.Although the LUMO level of the first hole injection layer 6 is lower than that of the second hole injection layer 7, the injection layer is thinner, allowing electrons to pass through quickly and be extracted by the anode 8. This electron extraction process significantly reduces the electron concentration of the hole transport layer 5, which on the one hand suppresses Auger recombination and recombination luminescence within the hole transport layer 5, thereby improving the device's luminous efficiency, and on the other hand increases the hole current, thus improving hole injection.

[0039] This device combines both light emission and photodetection modes within a single structure. Under forward bias, holes injected from the anode 8 and electrons injected from the cathode 2 enter the active layer 4 of the nanosheet via the hole transport layer 5 and electron transport layer 3, respectively. They meet and recombine within the nanosheet, emitting photons, thus functioning as a light-emitting diode. Under reverse bias, incident light is absorbed by the active layer 4, generating electron-hole pairs. These pairs are separated under a built-in electric field or an applied reverse bias and collected by corresponding electrodes via the electron transport layer 3 and hole transport layer 5, forming a photocurrent. In this mode, the device functions as a photodetector. Both modes share the same carrier selective transport channel; the polarity and magnitude of the bias voltage determine the direction of carrier flow. Therefore, the same device structure can simultaneously achieve both light emission and photodetection functions.

[0040] This application also provides a method for fabricating the above-mentioned nanosheet light-emitting detector, taking an inverted structure as an example, including steps S1 to S7: S1, depositing and patterning a cathode 2 on a substrate 1; S2, forming an electron transport layer 3 on the cathode 2; S3, forming a nanosheet active layer 4 on the electron transport layer 3; S4, forming a hole transport layer 5 on the nanosheet active layer 4; S5, forming a first hole injection layer 6 on the hole transport layer 5; S6, forming a second hole injection layer 7 on the first hole injection layer 6; S7, forming a patterned anode 8 by evaporation or sputtering on the second hole injection layer 7 in a vacuum environment. The electron transport layer 3, nanosheet active layer 4, hole transport layer 5, and first hole injection layer 6 in steps S2 to S5 can each be formed independently by any one of spin coating, blade coating, nanoimprinting, printing, and evaporation; the second hole injection layer 7 and anode 8 in steps S6 and S7 are preferably formed continuously by evaporation in a vacuum environment.

[0041] The steps for synthesizing the nanosheets provided in the embodiments of this application are described below.

[0042] A multi-step synthesis of (CdSe / CdS)@(2CdS / CdZnS) (core / crown)@(c-ALD shell / thermally injected shell) nanosheets was employed: Four monolayers (4 mL) of CdSe were used as the core, upon which a passivated CdS crown was deposited; subsequently, two monolayers (2 mL) of CdS intermediate layers were deposited via colloidal atomic layer deposition (c-ALD) to relax quantum confinement. The specific c-ALD method is as follows: First, a batch of core / crown nanosheets synthesized from a single crown was precipitated by adding ethanol and centrifugation, followed by redispersing in 1 mL of hexane. This process was repeated six times to remove all unreacted chemicals. Next, 1 mL of NMF (N-methylformamide) was added to the solution to allow phase separation between the NMF and hexane. Then, 75 μL of ammonium sulfide was added to the solution to cover the outer layer of the nanosheets, encapsulating their surface with sulfur atoms, thereby transferring the nanosheets into the NMF. After stirring for 3 minutes, hexane was removed by pipette, and additional toluene and acetonitrile were added for precipitation, followed by centrifugation. The nanosheets were redispersed in NMF again, and this precipitation / redispersion step was repeated twice. To promote cation growth, 2 mL of Cd(NO3)2·4H2O solution in NMF (1 M) was added to the nanosheet solution, and the mixture was stirred for 15–30 minutes. Subsequently, toluene and acetonitrile were added again, and the nanosheets were precipitated by centrifugation and then redispersed in NMF. The NMF process was repeated three times. To obtain the desired number of c-ALD shells, the process was repeated for each layer. This study designed for two monolayers (2 mL), so it was repeated twice. In the final step, 2 mL of OLA (oleylamine) was added to the precipitate and stirred at 50 °C for 2 minutes. The precipitate was then transferred to hexane for better ligand passivation. A thicker CdZnS alloy shell was then deposited by hot-injection to increase the thickness of the nanosheets. The intermediate CdS layer enhanced the compatibility between the core and the hot-injected shell. The CdS crown precursor solution was prepared by ultrasonically stirring 2.4 g of cadmium acetate dihydrate, 10 mL of 1-octadecene (ODE), and 1.7 mL of oleic acid (OA) at 150 °C until a uniform milky white color was obtained. During growth, 4 mL of CdSe core (OD stands for optical density, OD=1) was dispersed in 1 mL of hexane, mixed with 20 mL of ODE and 400 μL of OA, and degassed at 90 °C for 30 minutes. After purging with argon, a mixture of 2.4 mL of crown precursor solution and 400 μL of 0.1 mol / L thio-octadecene (S-ODE) was injected. The temperature was increased to 225 °C at 10 °C / min, and the mixture was immediately placed in a water bath for quenching. The temperature for hot-injection into the CdZnS shell was 300 °C, and the temperature was maintained for 60–120 minutes. The molar ratio of zinc acetate to cadmium acetate in the precursor was 4:1 (Zn:Cd).

[0043] See Figure 4 , Figure 4(a) is a transmission electron microscope (TEM) image of the nanosheets, by... Figure 4 (a) It can be seen that the synthesized nanosheets maintain a regular two-dimensional morphology; Figure 4 (b) shows the lateral size distribution of the nanosheets, derived from... Figure 4 (b) The average lateral dimension of the nanosheets was statistically determined to be 16.1 ± 1.6 nm; Figure 4 (c) shows the absorption and photoluminescence (PL) spectra of the nanosheets, derived from... Figure 4 (c) It can be seen that its absorption spectrum shows electron-heavy hole and electron-light hole transition peaks, PL emission peak is about 656 nm and Stokes shift is small; Figure 4 (d) shows the X-ray diffraction (XRD) pattern of the nanosheets, derived from... Figure 4 (d) It can be seen that the nanosheet is well crystallized, and its diffraction peak is slightly shifted relative to CdSe. The band gap of the nanosheet is about 1.97 eV (electric band gap obtained from energy level difference); it should be noted that the optical band gap obtained from the photoluminescence emission peak (about 656 nm) is about 1.89 eV. The difference of about 0.08 eV between the two is mainly due to the exciton binding energy and Stokes shift. Figure 4 The meanings of the English labels in each sub-figure are as follows: Count, Size, nm, Absorbance, PL intensity, Wavelength, au (arbitrary unit), Intensity, 2 Theta, and Degree. Figure 4 The scale bar in (a) is 50 nm. Figure 4 (b) indicates that 16.1 ± 1.6 nm is the average lateral dimension of the nanosheet and its standard deviation.

[0044] The fabrication and luminescent properties of light-emitting detectors are described below.

[0045] Using alkali-free glass as substrate 1, an ITO cathode 2, a ZnO electron transport layer 3, the aforementioned nanosheet active layer 4, a TCTA hole transport layer 5, a MoO3 first hole injection layer 6, a HAT-CN second hole injection layer 7, and an Al anode 8 were sequentially formed on it, resulting in an inverted device with an ITO (130 nm) / ZnO (40 nm) / nanosheet (35 nm) / TCTA (60 nm) / MoO3 (6 nm) / HAT-CN (6 nm) / Al (70 nm) structure. ZnO solution (concentration 15 mg / mL, dissolved in ethanol) was annealed at 150 °C for 15 min at 3000 rpm for 45 s. After annealing, the solution was cooled for 20 min, and then the nanosheet solution was spin-coated at 2000 rpm for 45 s. Finally, the device was subjected to a vacuum degree below 1×10⁻⁶. -4 The hole transport layer TCTA was deposited under Pa conditions, with the deposition rate controlled at 0.015–0.030 nm / s, resulting in a thickness of 60 nm. The thicknesses of both MoO3 and HAT-CN were preferably 6 nm, formed by continuous vacuum deposition at a rate of 0.01–0.015 nm / s. Finally, an Al electrode was deposited at a rate of 0.1–0.3 nm / s, resulting in a thickness of 70 nm. See [link to relevant documentation]. Figure 5 After employing a MoO3 / HAT-CN dual hole injection layer, the maximum luminance of the device reached 3782 cd / m². 2 This represents an improvement of approximately 24% compared to devices using only a single layer of MoO3; Figure 5 (a) is the current density-voltage-brightness curve, (b) is the external quantum efficiency-brightness curve, and (c) is the current efficiency-brightness curve. The on-state voltage decreased from 4.2V to 3.9V. The maximum external quantum efficiency (EQE) and current efficiency (CE) reached 13.91% and 4.87cd / A, respectively. Figure 5 (d) is the normalized electroluminescence spectrum, (e) is the electroluminescence spectrum under different driving voltages, and (f) is the CIE chromaticity coordinates. The electroluminescence peak of this device is located at 661 nm, the full width at half maximum (FWHM) is 27 nm, and the CIE 1931 chromaticity coordinates are (0.695, 0.265), indicating excellent color purity.

[0046] For comparison, devices with four hole injection structures—MoO3 / Al, HAT-CN / Al, HAT-CN / MoO3 / Al, and MoO3 / HAT-CN / Al—were fabricated, and the specific results are shown in Table 1. The results indicate that the device using the MoO3 / HAT-CN dual hole injection layer outperforms any single-layer configuration in terms of brightness, efficiency, and color purity, demonstrating that the dual hole injection layer structure can more effectively improve hole injection efficiency and charge injection balance.

[0047] Table 1

[0048]

[0049] The optical detection performance of the device is described below.

[0050] The photodetector behavior of the above devices under reverse bias was tested. Under -0.2V bias and dark conditions, the dark currents of the single-hole injection layer (MoO3 / Al) device and the double-hole injection layer (MoO3 / HAT-CN / Al) device were approximately 0.086 nA and 0.091 nA, respectively, which were similar, indicating that the potential barrier effectively suppressed electron injection under reverse bias. Furthermore, the noise power spectral density of the devices was measured under dark conditions and a -0.2V bias, with the measurement frequency range covering 1 Hz to 1 × 10⁻⁶. 5 The noise characteristics of single-hole injection layer devices and dual-hole injection layer devices are basically the same: in the low-frequency range, noise is mainly 1 / f noise, while in the high-frequency range, shot noise gradually becomes dominant; the noise power spectral density of both devices reaches its maximum value at 1 Hz, which is approximately 3 × 10⁻⁶. -22 The dark current fluctuation was A² / Hz, and then decreased with increasing frequency. These results indicate that the dark current fluctuations of both devices are very small. Combining the noise level and dark current, the specific detectivity of the devices at various wavelengths and optical power densities can be calculated, as shown in Table 2. The devices were illuminated with 405nm, 460nm, and 520nm lasers, with optical power densities of 50, 200, and 600 mW / cm² at 405nm, respectively. 2 The values ​​at 460nm are 7, 28, and 85 mW / cm². 2 The values ​​at 520nm are 1.7, 7, and 22 mW / cm². 2 The photon energy is sufficient to excite transitions from the valence band to the conduction band in the nanosheet. See also Figure 6 and Figure 7 As optical power density increases, the photocurrent response strengthens. With the laser on / off cycle set to 5s and the bias voltage maintained at -0.2V, the device can stably switch between photocurrent and dark current states across multiple cycles. (The last sentence appears to be incomplete and possibly refers to a different device.) -5 The time resolution measurements showed that the rise / fall times of the single-hole injection layer device at the three wavelengths were 0.12ms / 0.36ms, 0.13ms / 0.37ms, and 0.12ms / 0.40ms, respectively; while those of the dual-hole injection layer device were 0.14ms / 0.37ms, 0.16ms / 0.49ms, and 0.16ms / 0.46ms, respectively. This indicates a fast response time of 0.12–0.49ms. Figure 6 and Figure 7In the figure, (a) shows the current-voltage characteristics under dark and illuminated conditions at different wavelengths and optical power densities, (b) shows the single-cycle current response time curve, (c) shows the responsivity curve, (d) shows the multi-cycle current response time curve, and (e) shows the specific detectivity curve.

[0051] Table 2

[0052]

[0053] In other embodiments, the first hole injection layer 6 can also use WO3 or V2O5 instead of MoO3, as their work function is similar to that of MoO3, thus meeting the requirements of the first hole injection layer. The second hole injection layer 7 can also use a derivative of HAT-CN, which has a deep LUMO energy level similar to HAT-CN and can be prepared by vapor deposition. In addition, the device can also adopt an upright structure with the anode 8 disposed on the substrate 1, that is, from one side of the substrate outward, the sequence is anode (ITO), second hole injection layer, first hole injection layer, hole transport layer, nanosheet active layer, electron transport layer and cathode (Al or Ag), whose carrier transport path is symmetrical with the inverted structure, thus achieving the dual functions of light emission and photodetection.

[0054] The embodiments described above are merely examples of several implementation methods of this application, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of this patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these modifications and improvements all fall within the protection scope of this application.

Claims

1. A nanosheet light-emitting detector, characterized in that, The invention includes a substrate and a light-emitting detection stacked structure disposed on the substrate; the light-emitting detection stacked structure includes a cathode, an electron transport layer, a nanosheet active layer, a hole transport layer, a first hole injection layer, a second hole injection layer, and an anode, which are stacked sequentially.

2. The nanosheet light-emitting detector according to claim 1, characterized in that, The active layer of the nanosheets includes nanosheets prepared by solution method, and the nanosheets are quasi-type II heterojunction nanosheets with a core-crown structure.

3. The nanosheet light-emitting detector according to claim 1, characterized in that, The material of the first hole injection layer is one or more of MoO3, WO3 and V2O5.

4. The nanosheet light-emitting detector according to claim 1, characterized in that, The material of the second hole injection layer is one or more of HAT-CN and HAT-CN derivatives.

5. The nanosheet light-emitting detector according to claim 1, characterized in that, The absolute values ​​of the differences between the lowest unoccupied energy level of the first hole injection layer and the lowest unoccupied energy level of the second hole injection layer and the highest occupied energy level of the hole transport layer are both no greater than 0.6 eV, so that the first hole injection layer and the second hole injection layer extract electrons from the hole transport layer.

6. The nanosheet light-emitting detector according to claim 1, characterized in that, The second hole injection layer is located between the first hole injection layer and the anode, and the thickness of the first hole injection layer is 0.5-20 nm, while the thickness of the second hole injection layer is 1-200 nm.

7. The nanosheet light-emitting detector according to claim 1, characterized in that, The active layer of the nanosheet is configured to: serve as a light-emitting layer for electroluminescence under forward bias, and serve as a light-absorbing layer for absorbing incident light and generating photocurrent under reverse bias.

8. A method for fabricating a nanosheet light-emitting detector, characterized in that, The method for preparing the nanosheet light-emitting detector device according to any one of claims 1 to 7 comprises the following steps: forming a cathode on a substrate; forming an electron transport layer on the cathode; forming a nanosheet active layer on the electron transport layer; forming a hole transport layer on the nanosheet active layer; forming a first hole injection layer on the hole transport layer; forming a second hole injection layer on the first hole injection layer; and forming an anode on the second hole injection layer.

9. The preparation method according to claim 8, characterized in that, The electron transport layer, the nanosheet active layer, the hole transport layer, the first hole injection layer, and the second hole injection layer are each formed independently by any one of the following processes: spin coating, blade coating, nanoimprinting, printing, and vapor deposition.

10. The preparation method according to claim 8, characterized in that, The first hole injection layer, the second hole injection layer, and the anode are continuously formed by vapor deposition in a vacuum environment.